Preparation method of novel direct-writing type 3D printing high-strength mullite porous ceramic
The direct writing 3D printing method for mullite porous ceramics addresses energy inefficiencies and mold dependency in traditional processes by using specific raw materials and controlled sintering, achieving efficient and adaptable production of high-strength materials.
Patent Information
- Application Number
- CN202411417717.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2024-12-31
AI Technical Summary
Traditional preparation processes for mullite porous ceramics are energy-intensive, time-consuming, resource-wasteful, and reliant on complex mold manufacturing, making them unsuitable for rapid production and adaptation to changing needs.
A direct writing 3D printing method using alumina powder, silica fume powder, trisodium citrate, hydroxypropyl methylcellulose, polymethyl methacrylate microspheres, and mullite fiber wool, with controlled sintering to form a porous structure and avoid mold dependency.
The method reduces energy consumption, simplifies the process, and enables precise control over pore structure and material strength, adapting to various application requirements.
Smart Images

Figure CN119219401A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of high-temperature filtration technology, and in particular to a method for preparing a novel direct-writing 3D-printed high-strength mullite porous ceramic. Background Art
[0002] Mullite is an aluminum silicate mineral, which is widely used in the manufacture of high-temperature ceramic materials due to its excellent stability, low thermal expansion, good thermal shock resistance and chemical corrosion resistance at high temperatures. In particular, porous mullite ceramics are widely used in high-temperature filtration, thermal insulation materials, catalyst carriers and other fields due to their superior thermal isolation and high temperature resistance.
[0003] However, there are many technical difficulties in the traditional preparation process of mullite porous ceramics. First, the preparation of this type of ceramics often requires a high synthesis temperature, usually sintering at above 1500°C, which consumes a lot of energy and has a complex process. Secondly, the traditional porous ceramic preparation process relies on subtractive manufacturing, which requires removing materials to form a porous structure. This method is not only time-consuming, but also wastes resources. In addition, the use of molds further increases the complexity and cost of the process, and the mold manufacturing cycle is long, which makes it difficult to adapt to the needs of rapid production and changes. Summary of the invention
[0004] In view of the shortcomings of the prior art, the present invention provides a novel direct writing 3D printing method for preparing high-strength mullite porous ceramics, which solves the problems of high energy consumption, uneven pore distribution, insufficient strength and dependence on molds in the traditional preparation process of mullite porous ceramics.
[0005] To achieve the above objectives, the present invention is implemented by the following technical solutions: A new type of direct writing 3D printing high-strength mullite porous ceramics, including the following raw materials in percentage by mass:
[0006] Alumina powder: 20% to 40%;
[0007] Silica fume powder: 10% to 30%;
[0008] Trisodium citrate: 0.5%~2%;
[0009] Hydroxypropyl methylcellulose: 0.5% to 2%;
[0010] Polymethyl methacrylate microspheres: 30% to 50%;
[0011] Mullite fiber wool: 5%~15%.
[0012] Preferably, the pore structure of the mullite porous ceramic is formed by decomposition of polymethyl methacrylate microspheres during the sintering process.
[0013] Preferably, the particle size D50 of the alumina powder is 0.5 μm, the particle size D50 of the silica fume powder is 0.2 μm, and the mass ratio of alumina to silica fume is 1.35:1.
[0014] Preferably, the fiber diameter of the mullite fiber wool is 3 μm to 5 μm, the length is 10 mm to 20 mm, and the fibers are evenly distributed in the ceramic matrix.
[0015] Preferably, the addition ratio of trisodium citrate is 0.5% to 2% of the mixed powder.
[0016] A novel method for preparing high-strength mullite porous ceramics by direct writing 3D printing, comprising the following steps:
[0017] S1. Weigh alumina powder, silica fume powder, trisodium citrate, hydroxypropyl methylcellulose, polymethyl methacrylate microspheres and mullite fiber cotton in proportion;
[0018] S2. The alumina powder and silica fume powder were mixed, trisodium citrate and hydroxypropyl methylcellulose were added, and stirred into a slurry;
[0019] S3. Add polymethyl methacrylate microspheres and mullite fiber wool to the slurry and continue stirring;
[0020] S4. vacuum degassing the stirred slurry and loading it into a 3D printing device for direct writing printing to form a blank;
[0021] S5. After the green body is dried, sintering is performed according to a set sintering program.
[0022] Preferably, in step S3, a vacuum homogenizer is used to perform staged stirring at rotation speeds of 1500 r / min, 2000 r / min and 2500 r / min in sequence, with each stage stirring for 15 to 20 seconds, and the stirring is repeated multiple times.
[0023] Preferably, after stirring, the slurry is vacuum degassed at a speed of 1800 r / min for 90 seconds under a vacuum environment, and the process is repeated twice.
[0024] Preferably, the drying process in step S5 includes keeping in a constant temperature and humidity chamber for 24 hours, with the humidity decreasing from 100% to 70%, and the temperature increasing from 25°C to 40°C, and then drying in an oven at 50°C for 12 hours.
[0025] Preferably, the sintering process includes heating from room temperature to 200°C at 2°C / min, then heating to 550°C at 3°C / min and keeping warm for 60 minutes, then heating to 1200°C at 5°C / min, then heating to 1525°C at 3°C / min and keeping warm for 3 hours, and finally cooling to room temperature with the furnace.
[0026] The present invention provides a novel method for preparing high-strength mullite porous ceramics by direct writing 3D printing.
[0027] It has the following beneficial effects:
[0028] 1. The present invention adds polymethyl methacrylate microspheres to the ceramic slurry. The microspheres decompose to form a pore structure during the sintering process. The pore diameter and porosity can be adjusted by the particle size and content of the microspheres, so that the ceramic can adapt to different application requirements.
[0029] 2. The present invention uses trisodium citrate as a dispersant and hydroxypropyl methylcellulose as a binder to effectively avoid agglomeration of powder particles and ensure that the slurry has good fluidity and uniformity during the 3D printing process.
[0030] 3. The present invention adopts direct writing 3D printing technology to form the ceramic body, which avoids the time and resource investment required for traditional mold manufacturing, simplifies the preparation process, and shortens the preparation cycle. Through the controllable sintering program, the sintering of the material can be achieved under relatively precise temperature control, ensuring the stability of the material's microstructure and performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 It is a schematic diagram of the preparation method of the present invention. DETAILED DESCRIPTION
[0032] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] Example:
[0034] Please refer to the attached Figure 1 The embodiment of the present invention provides a novel direct writing 3D printing high-strength mullite porous ceramic, comprising the following raw materials in percentage by mass:
[0035] Alumina powder: 20% to 40%; the particle size D50 of the alumina powder is 0.5 μm.
[0036] Silica fume powder: 10% to 30%, the particle size D50 of silica fume powder is 0.2μm, and the mass ratio of alumina to silica fume is 1.35:1
[0037] Trisodium citrate: 0.5% to 2%; the addition ratio of trisodium citrate is 0.5% to 2% of the mixed powder
[0038] Hydroxypropyl methylcellulose: 0.5% to 2%;
[0039] Polymethyl methacrylate microspheres: 30% to 50%;
[0040] Mullite fiber wool: 5% to 15%. The fiber diameter of mullite fiber wool is 3μm to 5μm, the length is 10mm to 20mm, and the fibers are evenly distributed in the ceramic matrix.
[0041] The pore structure of mullite porous ceramics is formed by the decomposition of polymethyl methacrylate microspheres during the sintering process.
[0042] A novel method for preparing high-strength mullite porous ceramics by direct writing 3D printing, comprising the following steps:
[0043] Weigh the components of alumina powder, silica ash powder, polymethyl methacrylate microspheres, mullite fiber cotton, trisodium citrate and hydroxypropyl methylcellulose according to the designed proportion and put them into the mixing cup in sequence. First, alumina and silica ash are fully mixed in a mass ratio of 23:17. According to the designed proportion, polymethyl methacrylate microspheres are added to obtain a premixed powder. In addition, mullite fiber cotton is added to the premixed powder. The addition amount of binder and dispersant is 0.8wt.% of the mixed powder. Use a vacuum homogenizer for preliminary mixing at a low speed, and then add a certain amount of deionized water evenly to the premixed powder.
[0044] Place the mixing cup with the raw materials in a vacuum homogenizer, first stir at a low speed of 1500r / min for 15s to preliminarily mix the slurry, then stir at a speed of 2000r / min for 20s, and then stir at a high speed of 2500r / min for 20s, and repeat twice. Then set the homogenizer to a vacuum environment, stir at a speed of 1800r / min for 90s, and repeat twice, so that the slurry is centrifugally mixed and degassed under vacuum.
[0045] Fill the prepared slurry into the printing syringe of the printing equipment, put the filled syringe into the vacuum homogenizer again, stir at a speed of 2000r / min for 90s under vacuum environment for vacuum degassing, and repeat twice, the slurry preparation is completed. Before high-speed stirring and vacuum degassing, the stirring cup should be placed in ice water to fully cool down to avoid the slurry in the cup from generating heat due to high-speed rotation, friction between powder particles, or friction between powder particles and the cup wall, resulting in the slurry temperature being too high and the binder hardening, thereby making the slurry lose its printability.
[0046] Drying system
[0047] Set the temperature of the constant temperature and humidity chamber to 25°C and the humidity to 100% in advance. Place the printed embryo in the constant temperature and humidity chamber with the preset temperature and humidity for 24 hours. Within 24 hours, slowly reduce the humidity in the constant temperature and humidity chamber from 100% to 70%, and increase the temperature from 25°C to 40°C. Then take out the embryo and put it in an oven at 50°C for 12 hours to dry it thoroughly.
[0048] Sintering system
[0049] The experimental sintering system is as follows: starting from room temperature, heating up to 200°C at 2°C / min; then heating up to 550°C at 3°C / min, keeping at 550°C for 60 minutes for debinding; then heating up to 1200°C at 5°C / min; reducing the heating rate, heating up to 1525°C at 3°C / min, and keeping at this temperature for 3 hours; after the insulation is completed, cooling down to 1200°C at 3°C / min, and then cooling to room temperature and opening the furnace to take out the parts.
[0050] Embodiment 1:
[0051] Formula and proportion used:
[0052] Alumina powder: 30.05%;
[0053] Silica fume powder: 21.10%;
[0054] Trisodium citrate: 0.82%;
[0055] Hydroxypropyl methylcellulose: 0.82%;
[0056] Polymethyl methacrylate microspheres: 40.50%;
[0057] Mullite fiber wool: 6.70%.
[0058] Mullite porous ceramic effect:
[0059] Porosity: 50%;
[0060] Pore diameter: 15μm.
[0061] Conclusion: This embodiment is the best effect data, has good material properties, and meets the requirements of high strength and excellent pore structure.
[0062] Embodiment 2:
[0063] Formula and proportion used:
[0064] Alumina powder: 28.00%;
[0065] Silica fume powder: 22.00%;
[0066] Trisodium citrate: 1.00%;
[0067] Hydroxypropyl methylcellulose: 1.00%;
[0068] Polymethyl methacrylate microspheres: 42.00%;
[0069] Mullite fiber wool: 8.00%.
[0070] Mullite porous ceramic effect:
[0071] Porosity: 45%;
[0072] Pore diameter: 20μm.
[0073] Conclusion: In this embodiment, the ratio of alumina and polymethyl methacrylate microspheres is adjusted, and the pore structure is good.
[0074] Embodiment three:
[0075] Formula and proportion used:
[0076] Alumina powder: 35.00%;
[0077] Silica fume powder: 15.00%;
[0078] Trisodium citrate: 0.50%;
[0079] Hydroxypropyl methylcellulose: 0.90%;
[0080] Polymethyl methacrylate microspheres: 38.00%;
[0081] Mullite fiber wool: 5.00%.
[0082] Mullite porous ceramic effect:
[0083] Porosity: 48%;
[0084] Pore diameter: 25μm.
[0085] Conclusion: In this example, the alumina ratio is increased and the silica fume powder is reduced, resulting in an increase in pore diameter.
[0086] Embodiment 4:
[0087] Formula and proportion used:
[0088] Alumina powder: 25.00%;
[0089] Silica fume powder: 25.00%;
[0090] Trisodium citrate: 1.50%;
[0091] Hydroxypropyl methylcellulose: 1.50%;
[0092] Polymethyl methacrylate microspheres: 35.00%;
[0093] Mullite fiber wool: 7.50%.
[0094] Mullite porous ceramic effect:
[0095] Porosity: 52%;
[0096] Pore diameter: 22μm.
[0097] Conclusion: The proportion of this embodiment makes the material have moderate porosity and appropriate strength.
[0098] Embodiment five:
[0099] Formula and proportion used:
[0100] Alumina powder: 20.00%;
[0101] Silica fume powder: 30.00%;
[0102] Trisodium citrate: 1.50%;
[0103] Hydroxypropyl methylcellulose: 2.00%;
[0104] Polymethyl methacrylate microspheres: 50.00%;
[0105] Mullite fiber wool: 5.00%.
[0106] Mullite porous ceramic effect:
[0107] Porosity: 35%;
[0108] Pore diameter: 30μm.
[0109] Conclusion: In this embodiment, the proportion of polymethyl methacrylate microspheres is high and the porosity is low.
[0110] Embodiment six:
[0111] Formula and proportion used:
[0112] Alumina powder: 32.00%;
[0113] Silica fume powder: 20.00%;
[0114] Trisodium citrate: 0.75%;
[0115] Hydroxypropyl methylcellulose: 1.00%;
[0116] Polymethyl methacrylate microspheres: 30.00%;
[0117] Mullite fiber wool: 5.00%.
[0118] Mullite porous ceramic effect:
[0119] Porosity: 38%;
[0120] Pore diameter: 18μm.
[0121] Conclusion: This example forms relatively balanced material properties under different additive ratios.
[0122] Comparative Example 1:
[0123] Formula and proportion used:
[0124] Alumina powder: 15.00%;
[0125] Silica fume powder: 35.00%;
[0126] Trisodium citrate: 2.50%;
[0127] Hydroxypropyl methylcellulose: 1.50%;
[0128] Polymethyl methacrylate microspheres: 55.00%;
[0129] Mullite fiber wool: 12.00%.
[0130] Mullite porous ceramic effect:
[0131] Porosity: 25%;
[0132] Pore diameter: 18μm.
[0133] Conclusion: In this comparative example, the content of alumina is obviously insufficient and the content of polymethyl methacrylate microspheres is relatively high, resulting in a low porosity.
[0134] Comparative Example 2:
[0135] Formula and proportion used:
[0136] Alumina powder: 45.00%;
[0137] Silica fume powder: 5.00%;
[0138] Trisodium citrate: 0.25%;
[0139] Hydroxypropyl methylcellulose: 0.25%;
[0140] Polymethyl methacrylate microspheres: 20.00%;
[0141] Mullite fiber wool: 8.00%.
[0142] Mullite porous ceramic effect:
[0143] Porosity: 60%;
[0144] Pore diameter: 15μm.
[0145] Conclusion: In this comparative example, the content of silica fume powder is insufficient, which affects the strength and overall performance of the material. The experimental results are shown in the following table:
[0146]
[0147]
[0148] Summarize:
[0149] Embodiment 1
[0150] Formula: 30.05% alumina powder, 21.10% silica fume powder, 0.82% trisodium citrate, 0.82% hydroxypropyl methylcellulose, 40.50% polymethyl methacrylate microspheres, and 6.70% mullite fiber cotton.
[0151] Porosity: 50%; pore diameter: 15μm.
[0152] Evaluation: Optimal formulation with moderate porosity and small pore diameter, providing good strength and stability.
[0153] Recommended scenarios: high-temperature filtration, thermal insulation materials, high-strength structural parts, etc.
[0154] Embodiment 2
[0155] Formula: 28.00% alumina powder, 22.00% silica fume powder, 1.00% trisodium citrate, 1.00% hydroxypropyl methylcellulose, 42.00% polymethyl methacrylate microspheres, and 8.00% mullite fiber cotton.
[0156] Porosity: 45%; pore diameter: 20μm.
[0157] Evaluation: The porosity is moderate, but the pore diameter is slightly large, which affects the strength.
[0158] Recommended scenarios: lightweight insulation materials, filters and other applications, suitable for occasions where weight and strength requirements are not particularly stringent.
[0159] Embodiment 3
[0160] Formula: 35.00% alumina powder, 15.00% silica fume powder, 0.50% trisodium citrate, 0.90% hydroxypropyl methylcellulose, 38.00% polymethyl methacrylate microspheres, and 5.00% mullite fiber cotton.
[0161] Porosity: 48%; pore diameter: 25μm.
[0162] Assessment: Higher alumina ratio improves strength, but larger pore diameter affects thermal insulation performance.
[0163] Recommended scenarios: occasions requiring high strength and certain thermal insulation performance, such as high-temperature furnaces and supporting structures.
[0164] Embodiment 4
[0165] Formula: 25.00% alumina powder, 25.00% silica fume powder, 1.50% trisodium citrate, 1.50% hydroxypropyl methylcellulose, 35.00% polymethyl methacrylate microspheres, and 7.50% mullite fiber cotton.
[0166] Porosity: 52%; pore diameter: 22μm.
[0167] Evaluation: Balanced composition ratio, but higher porosity and pore diameter reduce overall strength.
[0168] Recommended scenarios: Used in situations where thermal insulation and lightweight are required, such as building insulation materials, household appliance insulation layers, etc.
[0169] Embodiment 5
[0170] Formula: 20.00% alumina powder, 30.00% silica fume powder, 1.50% trisodium citrate, 2.00% hydroxypropyl methylcellulose, 50.00% polymethyl methacrylate microspheres, and 5.00% mullite fiber cotton.
[0171] Porosity: 35%; pore diameter: 30μm.
[0172] Assessment: Lower alumina content results in insufficient strength and larger pore diameter affects thermal insulation performance.
[0173] Recommended scenarios: Suitable for low-strength and lightweight requirements, such as temporary insulation facilities or disposable filters.
[0174] Embodiment 6
[0175] Formula: 32.00% alumina powder, 20.00% silica fume powder, 0.75% trisodium citrate, 1.00% hydroxypropyl methylcellulose, 30.00% polymethyl methacrylate microspheres, and 5.00% mullite fiber cotton.
[0176] Porosity: 38%; pore diameter: 18μm.
[0177] Evaluation: Good strength, moderate porosity and small pore diameter, and relatively balanced overall performance.
[0178] Recommended scenarios: Structural applications in high temperature environments, such as industrial furnaces and furnace lining materials.
[0179] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A new type of direct writing 3D printing high-strength mullite porous ceramic, characterized in that: The following raw materials are included in mass percentage: Alumina powder: 20% to 40%; Silica fume powder: 10% to 30%; Trisodium citrate: 0.5%~2%; Hydroxypropyl methylcellulose: 0.5% to 2%; Polymethyl methacrylate microspheres: 30% to 50%; Mullite fiber wool: 5%~15%.
2. According to claim 1, a novel direct writing 3D printing high-strength mullite porous ceramic is characterized in that: The pore structure of the mullite porous ceramic is formed by decomposition of polymethyl methacrylate microspheres during the sintering process.
3. According to claim 1, a novel direct writing 3D printing high-strength mullite porous ceramic is characterized in that: The particle size D50 of the alumina powder is 0.5 μm, the particle size D50 of the silica fume powder is 0.2 μm, and the mass ratio of alumina to silica fume is 1.35:
1.
4. According to claim 1, a novel direct writing 3D printing high-strength mullite porous ceramic is characterized in that: The fiber diameter of the mullite fiber wool is 3 μm to 5 μm, the length is 10 mm to 20 mm, and the fibers are evenly distributed in the ceramic matrix.
5. According to the novel direct writing 3D printing high-strength mullite porous ceramics according to claim 1, it is characterized in that: The addition ratio of trisodium citrate is 0.5% to 2% of the mixed powder.
6. A novel method for preparing high-strength mullite porous ceramics by direct writing 3D printing, characterized in that: Using a novel direct writing 3D printing high-strength mullite porous ceramic according to any one of claims 1 to 5 comprises the following steps: S1. Weigh alumina powder, silica fume powder, trisodium citrate, hydroxypropyl methylcellulose, polymethyl methacrylate microspheres and mullite fiber cotton in proportion; S2. The alumina powder and silica fume powder were mixed, trisodium citrate and hydroxypropyl methylcellulose were added, and stirred into a slurry; S3. Add polymethyl methacrylate microspheres and mullite fiber wool to the slurry and continue stirring; S4. vacuum degassing the stirred slurry and loading it into a 3D printing device for direct writing printing to form a blank; S5. After the green body is dried, sintering is performed according to a set sintering program.
7. The method for preparing a novel direct writing 3D printing high-strength mullite porous ceramic according to claim 6, characterized in that: In step S3, a vacuum homogenizer is used to perform stage-by-stage stirring at rotation speeds of 1500 r / min, 2000 r / min, and 2500 r / min in sequence, with each stage being stirred for 15 to 20 seconds, and the stirring is repeated multiple times.
8. The method for preparing a novel direct writing 3D printing high-strength mullite porous ceramic according to claim 7, characterized in that: After stirring, the slurry was vacuum degassed at a speed of 1800 r / min for 90 seconds under a vacuum environment, and this process was repeated twice.
9. The method for preparing a novel direct writing 3D printing high-strength mullite porous ceramic according to claim 6, characterized in that: The drying process in step S5 includes keeping in a constant temperature and humidity chamber for 24 hours, with the humidity decreasing from 100% to 70% and the temperature increasing from 25°C to 40°C, and then drying in an oven at 50°C for 12 hours.
10. The method for preparing a novel direct writing 3D printing high-strength mullite porous ceramic according to claim 6, characterized in that: The sintering process includes heating from room temperature to 200°C at 2°C / min, then heating to 550°C at 3°C / min and keeping it for 60 minutes, then heating to 1200°C at 5°C / min, and then heating to 1525°C at 3°C / min and keeping it for 3 hours, and finally cooling to room temperature with the furnace.
Citation Information
Patent Citations
Preparation method of aperture adjustable porous metal oxide based on molecular layer deposition
CN110512189A
Porous heat-insulating ceramic material with closed-pore structure and preparation method of porous heat-insulating ceramic material
CN114315410A
